Manufacturing biological medicines on demand: Safety and efficacy of granulocyte colony‐stimulating factor in a mouse model of total body irradiation. (6th February 2020) - Adiga, Rajani; Andar, Abhay; Borhani, Shayan; Burgenson, David; Deldari, Sevda; Frey, Douglas; Ge, Xudong; Gopalakrishnan, Mathangi; Gurramkonda, Chandrasekhar; Gutierrez, Erick; Jackson, Isabel L.; Kostov, Yordan; et al.
Abstract: Protein therapeutics, also known as biologics, are currently manufactured at centralized facilities according to rigorous protocols. The manufacturing process takes months and the delivery of the biological products needs a cold chain. This makes it less responsive to rapid changes in demand. Here, we report on technology application for on‐demand biologics manufacturing (Bio‐MOD) that can produce safe and effective biologics from cell‐free systems at the point of care without the current challenges of long‐term storage and cold‐chain delivery. The objective of the current study is to establish proof‐of‐concept safety and efficacy of Bio‐MOD‐manufactured granulocyte colony‐stimulating factor (G‐CSF) in a mouse model of total body irradiation at a dose estimated to induce 30% lethality within the first 30 days postexposure. To illustrate on‐demand Bio‐MOD production feasibility, histidine‐tagged G‐CSF was manufactured daily under good manufacturing practice‐like conditions prior to administration over a 16‐day period. Bio‐MOD‐manufactured G‐CSF improved 30‐day survival when compared with saline alone ( p = .073). In addition to accelerating recovery from neutropenia, the platelet and hemoglobin nadirs were significantly higher in G‐CSF‐treated animals compared with saline‐treated animals ( p < .05). The results of this study demonstrate the feasibility of consistently manufacturing safe and effective on‐demand biologics suitable for real‐time release.